2021
DOI: 10.3208/jgssp.v09.cpeg128
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity of municipal solid waste based on inverse analysis of in-situ heat extraction test

Abstract: In this study, a two-dimensional finite difference model was used to simulate the heat transfer occurred during a 17-day heat extraction test performed in an MSW landfill cell in Santee, California. The heat extraction was performed using serpentine horizontal heat exchangers installed 6 m above the base liner of the cell, and it started after the waste reached a stable temperature value of 52 °C. The model was developed based on the differential heat conduction equation and an inverse analysis was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Further, from Table 1, it can be observed that the k of the MSW varies between 0.01 and 1.50 W/(m K) (Bonany et al, 2013;Hanson et al, 2008;Yeşiller et al, 2015;Manjunatha et al, 2020;Nocko et al, 2021), which is, in general, higher than that of dry inorganic soils (k=0.27-0.38 W/m K) (Mondal et al, 2016(Mondal et al, , 2017. Such a higher value can be due to the higher moisture content and electrical conductivity of the leachate (Grellier et al, 2006), which is proportional to k (Schwarz and Bertermann, 2020).…”
Section: Thermal Properties Of Msw: Guiding Factor Of Landfill Firesmentioning
confidence: 92%
See 2 more Smart Citations
“…Further, from Table 1, it can be observed that the k of the MSW varies between 0.01 and 1.50 W/(m K) (Bonany et al, 2013;Hanson et al, 2008;Yeşiller et al, 2015;Manjunatha et al, 2020;Nocko et al, 2021), which is, in general, higher than that of dry inorganic soils (k=0.27-0.38 W/m K) (Mondal et al, 2016(Mondal et al, , 2017. Such a higher value can be due to the higher moisture content and electrical conductivity of the leachate (Grellier et al, 2006), which is proportional to k (Schwarz and Bertermann, 2020).…”
Section: Thermal Properties Of Msw: Guiding Factor Of Landfill Firesmentioning
confidence: 92%
“…Biochemical decomposition of MSW in the landfills affects the temperature rise during the LFs and vice versa. The heat generated during these processes (i) accumulates, which subsequently results in smouldering (the slow, flameless form of combustion), or spontaneous landfill fires when the rise in temperature reaches the ignition point (Chavan et al, 2019), (ii) dissipate into the surrounding environment and (iii) can be extracted (depending on the amount) for direct heating of nearby residential and industrial facilities (Nocko et al, 2021). In all these cases, the heat accumulated in the landfills cannot be dissipated naturally through their covers and slopes, and heat exchangers can be used to extract the thermal energy from the landfills (Coccia et al, 2013;Shi et al, 2018).…”
Section: Thermal Properties Of Msw: Guiding Factor Of Landfill Firesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that, in North America and Europe, MSW landfill temperatures can be about 35°C higher than that of typical shallow soil profiles [5,6], and may rise above 65°C as a result of the anaerobic MSW biodegradation [1]. A few studies have even assessed the implementation of geothermal technology for harvesting shallow geothermal energy at landfills [8,9].…”
Section: Introductionmentioning
confidence: 99%